Community Service for Cianjur Earthquake Victims Through Education and Empowerment - Khaerudin, Khaerudin (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research aims to discuss community service and concern for earthquake victims that occurred in Cianjur. Want to analyze the process of community service for victims of the Cianjur earthquake and want to know the level of concern from volunteers for the victims of the Cianjur earthquake. The research method uses a qualitative approach that describes the phenomena observed at the research location. The technique of collecting data is through direct field surveys for victims of the Cianjur disaster. Interviews by asking questions of volunteers and disaster victims, who were visited at the service location. Documentation studies of television media and internet media, information from volunteers, officials and other communities. Results and conclusions: (1). In the implementation of community service and concern from community volunteers from West Java, Banten and Jakarta to help and lighten their burden, from various institutions and communities. With various vehicles carrying aid in the form of food supplies, clothes, medicines and in the form of funds for the Cianjur earthquake victims. (2). Implementation of community service through education for school-age children in the form of education on traumatic healing, reading and writing the Koran, giving light questions about learning, singing, giving gifts of toys and food in the form of textbooks, dolls and other toys. Community service in the form of road repairs and lighting for power outages. Distribution of groceries, women's clothing, men's clothing and children's clothing, free medical and health care.